The macroeconomics originator of foreign direct investment (FDI) in Malaysia / Faiszuan Mohd Salleh and Nur Atikah Adzahar - Mohd Salleh, Faiszuan; Adzahar, Nur Atikah (Faculty of Business Management, 2016)
The strong growth performances experienced by Malaysia economy greatly depends on the Foreign Direct Investment (FDI). FDI is basically generates economic growth by increasing the formation of capital through the expansion of production capacity, promotion of export growth and creation of employment in Malaysia. This research is aimed empirically investigate the relationship between Foreign Direct Investment (FDI) and macroeconomics variables such as exchange rates, interest rates, import, export and foreign exchange reserves in Malaysia by conduct a test on annual data set of sample size 30 over the period of 1985 to 2015. FDI inflows in Malaysia had massively fluctuated from year 1996 to 2010 and later. Therefore, this extensive volatility drew the researchers’ attention to scrutinize the cause that affecting FDI inflows in Malaysia. In regards to this research, Multiple Linear Regressions model is applied to find the relationship between the considered variables. This paper primarily attempt to examine import, export and reserves towards FDI in Malaysia. Although there are many factors have influenced FDI in Malaysia generally, it is still not clear if these factors will also be the huge contribution to the FDI inflows in Malaysia.